2014
DOI: 10.1152/jn.00055.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic EPSCs and their potentiation by bradykinin in single paratracheal ganglion neurons attached with presynaptic boutons

Abstract: We have found that bradykinin (BK) potentiates the nicotine-induced currents in airway paratracheal/parabronchial ganglia (PTG) neurons. In this study, we investigated if BK affects the cholinergic synaptic transmission in rat PTG neurons attached with synaptic buttons. Excitatory postsynaptic currents (EPSCs) were recorded in acutely dissociated PTG neurons attached with presynaptic boutons. EPSC frequency was increased in the high-K(+) external solution without affecting their amplitude. Activation and deact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…; Zhou et al . ). These boutons could possibly still respond to acidosis by releasing neurotransmitters, so that even some of the residual pH response seen in dissociated RTN neurons (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Zhou et al . ). These boutons could possibly still respond to acidosis by releasing neurotransmitters, so that even some of the residual pH response seen in dissociated RTN neurons (Wang et al .…”
Section: Discussionmentioning
confidence: 97%
“…We also found that bradykinin, a potent inflammatory peptide, depolarized the membrane potential via inhibition of M-type K ϩ channels and induced action-potential generation in acutely dissociated paratracheal ganglia neurons (27). Furthermore, bradykinin potentiated the nicotinic current and cholinergic excitatory postsynaptic currents (EPSCs) in the neurons (47,48). Thus the paratracheal ganglia may serve as critical sites for the pathogenesis of airway inflammation associated with cough.…”
mentioning
confidence: 92%
“…The cocaine-induced reduction of sEPSCs observed in this study may be at least partly account for the reduced activity of mPFC neurons recorded after cocaine administration in rats in vivo. 12) The reduction of mPFC neuronal activity may be related to cocaine-induced hypofrontality, in which mPFC neuronal responses to cocaine and cocaine-associated cues are amplified. 12) Thus, our finding might be one of the mechanisms for generating hypofrontality, which is critically involved in the development of cocaine addiction.…”
Section: Discussionmentioning
confidence: 99%
“…11) In support of this finding, acute cocaine administration decreases neuronal activity in the rat mPFC. 12) These cocaine-induced changes, so-called hypofrontality, may contribute to the development of cocaine addiction. However, the mechanism(s) underlying these inhibitory effects of cocaine remains unclear.…”
Section: Introductionmentioning
confidence: 99%